The Quality Of The Papuan Cultural Studies And Modernization (PBPM) Program At Sekolah Anak Indonesia (SAI) Sentul Bogor - Edmundus Bawor; Masduki Ahmad ; Desi Rahmawaty (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The PBPM program is part of the development of operational school curricula specifically for students from Papua by highlighting local wisdom values and modernization knowledge as the main learning outcomes that must be mastered by students in order to master certain competencies. PBPM aims to introduce Papua culture to Papua students and provide them with the skills needed to compete in the global world. PBPM is implemented at the Indonesian Children's School (SAI) Sentul Bogor, which is a boarding school for Papua students. The method used is a descriptive qualitative approach to describe and explain the implementation of the Papua Culture and Modernization Study Program (PBPM) at the Indonesian Children's School (SAI) Sentul Bogor. The PBPM research program at the Indonesian Children's School (SAI) Sentul Bogor uses data collection techniques in the form of documentation, interviews, and observation reviews and conducts interviews with 17 informants consisting of school principals, deputy principals for curriculum, teachers, administrative staff, and students. The results showed that PBPM uses a skill-based approach and utilizes existing local assets. Students learn about Papua culture through various activities, such as conducting Papua reality studies and seven cultural elements, which are then assisted by modern science-based skills such as agriculture, animal husbandry, language, and technology. PBPM has provided many benefits for Papua students and the community. Students who participate in PBPM have shown improvements in both academic and non-academic achievements. PBPM also serves as a means of transformation for Papua students from the traditional system to modernization without leaving their culture, so that Papua students are relevant in globalization and able to compete in the 21st century.